The structure of philosophical discourse a genre and move analysis - Lucas, Kyle; Lucas, Sarah (Lecturer in philosophy) (New York, NY : Routledge, 2024)
This book builds on existing work in genre analysis and move analysis in English for Specific Purposes (ESP) and applies this new framework to academic philosophical discourse, offering new insights into how ESP traditions can elucidate shifts in language conventions across disciplinary contexts. The volume begins by surveying the state of the art in English for Specific Purposes and genre theory, as well as other genre theory paradigms before turning the focus on move analysis. Lucas and Lucas seek to maximize the potential of move analysis to precisely operationalize functional units of discourse by implementing a cognitive theory of genre grounded in frame semantics. Using the case of academic research articles in philosophy, the authors demonstrate how this framework can reveal distinctive dimensions unique to philosophical discourse and, in turn, how such an approach might be applied more broadly to examine nuances in language across disciplines and inform ESP research in the future. This book will appeal to students and researchers in English for Specific Purposes, discourse analysis, academic writing, applied linguistics, and rhetoric and composition.
Keywords: Philosophy -- Authorship; Academic writing; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics